Entertainment Factor and Relatability’s Effect on Gen Z and Millennial’s Interaction in Medan Through Their Emotion - Ayu Nur Utami Siwi Hariyati; Arlina Nurbaity Lubis; Beby Karina Fawzeea (Mutiara: Multidiciplinary Scientifict Journal, 2024)
The fashion industry experiences rapid development in today’s era and intense competition to attract consumer interaction cannot be avoided. High consumer interaction can secure a high interest for a company and high interaction is needed to remain relevant and achieve desired targets. This study aims to determine and analyze the effect of entertainment factors and relatability in fashion brands’ social media marketing content on consumer interaction through personal emotion on Genz and Millennial in Medan. This research is quantitative and associative, with data collected from the documented study and a questionnaire. The population in this study were all online shopping consumers from age 18 to 35 who have one social media account on Facebook/X/Instagram/TikTok and live in Medan. The sampling method used in this study is non-probability convenience sampling, with 180 respondents taken from five areas in Medan. This study used path analysis to analyze the data. The results from this study show that the entertainment factor has a significant effect on personal emotion, both positive and negative, but no significant effect on consumer interaction. However, the entertainment factor indirectly affects consumer interaction through negative personal emotions, not positive ones. Relatability has a significant effect on positive emotion, which also has a direct significant effect on consumer interaction and a significant effect mediated through positive personal emotion, yet relatability does not influence the negative one, directly and indirectly. Personal emotions, both positive and negative, have a significant effect on consumer interaction.